Pengaruh Independensi dan Kompetensi Terhadap Kualitas Audit (Studi Empiris Pada Kantor Akuntan Publik di Bandung) - Sendie Nur Hidayat; Rini Susiani (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to determine and analyze the effect of auditor independence and competence on audit quality at Public Accounting Firms in Bandung. This study data was obtained by distributing questionnaires to 45 respondents using the quota sampling technique, which is part of Non-probability Sampling. Respondents in this study were auditors at the Public Accounting Firm in Bandung. The analysis technique used in this research is the classical assumption test, multiple linear regression, and hypothesis testing. The results showed that independence has a positive but insignificant effect on audit quality, competence has a positive and significant effect on audit quality, and independence and competence simultaneously have a significant effect on audit quality. Keywords: Independence, Competence, Audit Quality